Faktor-faktor yang Mempengaruhi Persistensi Laba - Ainun Uswatul Khasanah; Jasman (JRB-Jurnal Riset Bisnis, 2019)
This research aims to determine the effect of independent cash flow volatility, sale volatility, operating cycle, level of debt, size of firm and book tax differences in earnings persistence. The data used in this research is obtained from the annual report of financial statements on manufacturing companies listed in the Indonesian Stock Exchange period 2015-2017. Sample selection method used is purposive sampling method. Analytical techniques used in this research using multiple linear regression which include normality test, test classic assumptions and hypothesis testing. The total sample in this research is 49 companies. The result shows thatI cash flow voaltility, sale volatility, level of debt, size of firm and temporer different have an affect on earnings persistence. Meanwhile, the operating cycle and permanent different no effect on earnings persistence.